Biofortification of Oryza sativa L. with agri-food waste to improve the dietary value of crops - Ziarati, Paris; Moradi, Donya; Rodriguez, Luis Cruz; Hochwimmer, Bernhard; Vambol, Viola; Vambol, Sergij (Ecological Questions, 2021)
Due to the low dietary value of crops, Zn-deficient soils and insufficient intake of other minerals, soil fortification is often necessary. Fortification is defined as the addition of one or more crucial nutrients to a food to reduce poverty in a population or specific population groups. Currently available technologies for rice fortification with vitamins and minerals are high-energy and time-consuming methods. Therefore, mineral enrichment of crops has received much attention from scientists. The originality of the current study consists in determining the optimal use of hard hazelnut shells, orange peel and rice husks for enrichment of paddy soil and simultaneous immobilization of heavy metals. The combination of the identified wastes, namely hazelnut shells, orange peel and rice husks, showed good potential for immobilization/elimination or reduction of heavy metals to less than permissible limits. Therefore, the use of this combination could be an effective strategy to both introduce new micronutrients into rice grain and remove heavy metals.